Disruption of focal adhesions by Clostridioides difficile TcdB variants - Deida Loáiciga-Rodríguez; Iveth Jiménez-Badilla; Carlos Quesada-Gómez (International Journal of Cell and Biomedical Science, 2026)
Background: Clostridioides difficile infection (CDI) is a leading cause of antibiotic-associated nosocomial diarrhea, with disease severity predominantly influenced by the activity of toxin B (TcdB). Although TcdB-mediated inactivation of Rho family GTPases is well established, the downstream consequences for cell–matrix adhesion architecture remain poorly defined. Objective: This study examined how TcdB variants with distinct substrate specificities (VPI 10463, NAP1/RT027, and NAP1v/RT019) disrupt focal adhesion organization and cytoskeletal integrity. Results: Purified TcdB variants were standardized by functional equipotency and applied to HeLa cells. While most structural adhesion proteins, including talin and zyxin, demonstrated quantitative stability, plectin exhibited a selective and progressive loss following exposure to RhoA-inactivating toxins. Concurrently, paxillin phosphorylation was significantly diminished, and co-immunoprecipitation analyses disclosed a substantial dissociation of paxillin from pivotal adhesion components, with no indication of global proteolytic degradation. Morphological outcomes correlated with toxin substrate specificity: RhoA-inactivating variants resulted in cell rounding, while NAP1v promoted an arborizing phenotype. Conclusion: Collectively, these findings suggest that TcdB variants predominantly induce a biochemical disassembly of focal adhesion complexes rather than widespread protein degradation. This adhesion uncoupling mechanism may represent a molecular framework linking toxin specificity to epithelial barrier disruption and could potentially be associated with differences in clinical severity among CDI strains.